THE IMPACT OF TECHNOLOGICAL DEVELOPMENTS ON EMPLOYMENT LAW REGULATIONS - Andreas Kevin Simanjorang; Catharina Dewi Wulansari (RADJA PUBLIKA, 2025)
The rapid development and advancement of technology in recent decades have had a significant impact on various aspects of life, including the employment sector. Technological changes such as automation, artificial intelligence, robotics, and digitalization have fundamentally altered the work landscape. Consequently, employment law regulations need to be adjusted to address emerging new challenges and protect workers' rights. Technological changes such as automation, artificial intelligence, robotics, and digitalization have fundamentally changed the work landscape. Consequently, employment law regulations need to be adjusted to address emerging new challenges and protect workers' rights. This study aims to examine the impact of technological changes on employment law regulations. Flexible work concepts, such as remote work and temporary work contracts, are becoming increasingly common with the adoption of digital technology. Employment law regulations need to accommodate this flexible work by taking into account technological changes, employment law regulations, the impact of technological changes on employment relationships, and how employment law regulations can be adjusted to remain relevant and protect workers in an era of technological change.